1998
DOI: 10.1091/mbc.9.8.2217
|View full text |Cite
|
Sign up to set email alerts
|

ATP- and Cytosol-dependent Release of Adaptor Proteins from Clathrin-coated Vesicles: A Dual Role for Hsc70

Abstract: Clathrin-coated vesicles (CCV) mediate protein sorting and vesicular trafficking from the plasma membrane and the trans-Golgi network. Before delivery of the vesicle contents to the target organelles, the coat components, clathrin and adaptor protein complexes (APs), must be released. Previous work has established that hsc70/the uncoating ATPase mediates clathrin release in vitro without the release of APs. AP release has not been reconstituted in vitro, and nothing is known about the requirements for this rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
65
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 55 publications
5
65
0
4
Order By: Relevance
“…Similarly, neither AP1 nor GGA dissociated with the clathrin from the TGN. These results are consistent with the observation of Hannan et al, who suggested that, Hsc70 is in some way necessary for dissociation of AP2 from CVs, but it is not sufficient (Hannan et al, 1998). A cofactor in cytosol, which has recently been identified by Ghosh et al to be a phosphatase, has been shown to be required for dissociation of AP1 from CVs (Ghosh et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, neither AP1 nor GGA dissociated with the clathrin from the TGN. These results are consistent with the observation of Hannan et al, who suggested that, Hsc70 is in some way necessary for dissociation of AP2 from CVs, but it is not sufficient (Hannan et al, 1998). A cofactor in cytosol, which has recently been identified by Ghosh et al to be a phosphatase, has been shown to be required for dissociation of AP1 from CVs (Ghosh et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…However, this effect may occur because GFP-Hsp70(K71E) becomes completely immobilized in the nucleus and partially immobilized in the cytosol during heat shock. By contrast, in untreated cells, GFP-Hsp70(K71E) is only slightly less mobile than GFP-Hsp70 and, therefore, its slow rate of transport into and out of the nucleus is probably either because of its inability to bind ATP tightly and hydrolyze it (O'Brien et al, 1996) or because of its related tendency to oligomerize with itself in vitro (Rajapandi et al, 1998) and with Hsp70 in vivo (Hannan et al, 1998). This tendency to oligomerize could also explain why expression of Hsp70(K71E) had a trans-dominant effect on GFP-Hsp70 transport into and out of the nucleus before heat shock and why it prevented these rates from changing during heat shock.…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitous binding partners of HSP70 include a wide range of unfolded peptides as well as native proteins. Two native proteins found in the nerve terminal that bind with the constitutively expressed member of the heat shock protein 70 family, HSC70, are the clathrin triskelions of coated vesicles (33,34) and the intrinsic synaptic vesicle protein, CSP (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%